Desain dan Implementasi Aplikasi Layanan Bimbingan Konseling Siswa di SMA Ibrahimy Wongsorejo - Ulil Fajriyah; Abd. Ghofur; Hermanto (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2022)
The use of information technology in student counseling services at Ibrahimy Wongsorejo High School is very important to be built and developed based on the current business process of counseling guidance services which still use conventional media in the form of paper, resulting in consuming a lot of space, time and cost. In addition, counselors must recapitulate all data on violations and student achievements every month so that an information system is needed that helps counseling guidance services. This study aims to design and build a web-based counseling guidance information system. The system development method used is the Waterfall method. The information system built can process student data, parent data and student guidance data. Besides that, counselors and principals can see the history of counseling guidance carried out directly by students at school.